Digital Movement of Opinion Analysis in Social Media X: The Rohingnya Refugees - Huda, Anam Miftakhul; Tsuroyya, Tsuroyya; Nurwahid, Aditya Fahmi; Firmannandya , Ade; Miarta, Wahyu Mahesa; Syahputra, Alif Nizar; Ismail, Adibah binti (Komunikator, 2025)
The expansion of social media has generated increasingly dynamic and spontaneous digital opinion movements, particularly on humanitarian issues such as the Rohingya refugee crisis. As a persecuted minority facing systemic discrimination in Myanmar, the Rohingya have become the subject of intense discussion on Social Media X (formerly Twitter). This study focuses on the structure of the communication network, identification of key actors, information-dissemination patterns, and temporal dynamics of conversations throughout 2023. Data were collected using Indonesian-language tweets retrieved with the keyword “Rohingya lang:id” and analyzed using NodeXL. The results show that public opinion was dispersed across more than 45,185 accounts, 116,415 interactions, and approximately 2,000 discussion clusters, yet was predominantly shaped by replies and mentions from low-influence accounts. Conversation intensity peaked in December 2023, triggered by on-the-ground events in Aceh. Negative sentiment dominated (49%), reflecting a trend of Indonesian netizens expressing ridicule toward Rohingya refugees. The absence of influential actors—such as President Jokowi or UNHCR Indonesia—combined with the massive volume of discourse generated by non-influential users resulted in an uncontrolled spread of narratives. This study recommends strengthening the monitoring of digital opinion movements to support more responsive and evidence-based policymaking on refugee issues.